Age‐differences in network models of self‐regulation and executive control functions. Issue 5 (18th May 2022) - Neubeck, Markus; Johann, Verena E.; Karbach, Julia; Könen, Tanja
Abstract: Self‐regulation (SR) and executive control functions (EF) are broad theoretical concepts that subsume various cognitive abilities supporting the regulation of behavior, thoughts, and emotions. However, many of these concepts stem from different psychological disciplines relying on distinct methodologies, such as self‐reports (common in SR research) and performance‐based tasks (common in EF research). Despite the striking overlap between SR and EF on the theoretical level, recent evidence suggests that correlations between self‐report measures and behavioral tasks can be difficult to observe. In our study, participants from a life‐span sample (14–82 years) completed self‐report measures and behavioral tasks, which were selected to include a variety of different facets of SR (e.g., sensation seeking, mindfulness, grit, or eating behavior) and EF (working memory, inhibition, shifting). Using this broad approach, we systematically investigated connections and overlap of different aspects of SR and EF to improve their conceptual understanding. By comparing network models of a youth, middle‐aged, and older‐aged group, we identified key variables that are well connected in the SR and EF construct space. In general, we found connections to be stronger within the clusters of SR and EF than between them. However, older adults demonstrated more connections between SR and EF than younger individuals, likely because of declining cognitive resources. Abstract : Different network structures of self‐regulation (SR) and executive functions (EF) were found for a youth, middle‐aged, and older‐aged group of a lifespan sample. Connections were stronger within clusters of different aspects of SR and EF than between them (see Figure). Older adults demonstrated more connections between SR and EF than younger individuals, likely because of declining cognitive resources.